Evaluation of an integrated wood-burning stove with water tank system for heating rural homes in the Andean highlands of Peru - Soria L.S.G. (2020)
In this work, we study an improved wood-burning stove with a water tank placed in the flue gas outlet for use as a heater. This system takes advantage of the waste heat of the gases that pass through the chimney to heat the water contained in the tank. The evaluations were carried out in a house located in the district of San Antonio de Chuca (Imata), province of Caylloma, department of Arequipa, Peru, located above 4500m above sea level, where temperatures decrease to -20 °C during winter. A method is proposed to measure the power input of the integrated tank, which consists of finding the maximum power that the flue gas delivers to the water in the tank when the stove is turned on. Once this power has been identified, the wood-burning stove is replaced by an electric heating system that delivers the same power to heat the water. Once the electrical system has been calibrated, the water in the tank is heated to different temperatures, and the following are calculated: the accumulated energy, the time needed to reach the desired temperature and the amount of wood that would be used if the kitchen were used for heating. The power that the heater can deliver to the test house is thus determined. If the water in the tank is heated to 70 °C, this heating system can deliver an average power value of 450 W from 20:00 to 5:00 the next day. © Published under licence by IOP Publishing Ltd.